2008
DOI: 10.1007/s11606-008-0655-4
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Duration of Vasomotor Symptoms of Menopause: A Meta-Analysis

Abstract: Our findings suggest a median symptom duration of about 4 years among symptomatic women. A longer symptom duration may affect treatment decisions and clinical guidelines. Further prospective, longitudinal studies of menopausal symptoms should be conducted to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 47 publications
(36 reference statements)
3
115
1
14
Order By: Relevance
“…Silent myocardial ischemia was 2.2 times more common in diabetics as compared to nondiabetics. 11 Another Indian study by Gupta et al reported 38.3% of diabetics without prior coronary artery disease had silent myocardial ischemia on exercise test. 12 In present study, cases with BMI 18.5-24.9 (Normal), 25-29.9 (Over weight) and > 30 (Obese), 7, 1 and 1 were TMT positive respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Silent myocardial ischemia was 2.2 times more common in diabetics as compared to nondiabetics. 11 Another Indian study by Gupta et al reported 38.3% of diabetics without prior coronary artery disease had silent myocardial ischemia on exercise test. 12 In present study, cases with BMI 18.5-24.9 (Normal), 25-29.9 (Over weight) and > 30 (Obese), 7, 1 and 1 were TMT positive respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Тот факт, что использо-вание низких доз эстрогенов связано с увеличением ри-ска развития гиперплазии эндометрия по сравнению с употреблением плацебо при длительности приема в те-чение одного года, не подтвержден крупными рандоми-зированными исследованиями. Существуют различные причины использования низких доз гормонов с целью облегчения симптомов менопаузального синдрома (МС) [25,26]. Во-первых, женщинам, возможно, потребуется принимать МГT в течение длительного времени, так как в настоящее время считается, что средняя продолжи-тельность симптомов МС составляет 4 года [6].…”
Section: рекомендации для практикиunclassified
“…В связи с этим важным является использо-вание комбинации самой низкой возможной дозы эстро-гена и прогестагена. Представленные результаты науч-ных исследований помогут врачам назначать низкодози-рованные препараты МГТ не только для купирования симптомов МС [25], но и для защиты эндометрия. Влия-ние трансдермального и внутриматочного применения гормонов на риск развития опухолевых новообразова-ний в органах репродуктивной системы требует дальней-шего изучения.…”
Section: рекомендации для практикиunclassified
“…Долгое время бытовала точка зрения, что приливы длятся в течение 0,5-2 лет [5]. Однако Мельбурнское исследование здоровья женщин определило большую, до 5 лет, продолжительность приливов [6], а в мета-анализе, включившем 10 исследований приливов жара, медиана продолжительно-сти равнялась 4 годам [7]. В том же мета-ана-лизе было установлено, что у 10% пациенток приливы сохраняются по истечении 12 лет после менопаузы.…”
Section: Introductionunclassified